The PREDICT study uncovers three clinical courses of acutely decompensated cirrhosis that have distinct pathophysiology - ÖZDOĞAN, OSMAN CAVİT (ELSEVIER, 2020)
Background & Aims: Acute decompensation (AD) of cirrhosis is defined as the acute development of ascites, gastrointestinal hemorrhage, hepatic encephalopathy, infection or any combination thereof, requiring hospitalization. The presence of organ failure(s) in patients with AD defines acute-on-chronic liver failure (ACLF). The PREDICT study is a European, prospective, observational study, designed to characterize the clinical course of AD and to identify predictors of ACLF. Methods: A total of 1,071 patients with AD were enrolled. We collected detailed pre-specified information on the 3-month period prior to enrollment, and clinical and laboratory data at enrollment. Patients were then closely followed up for 3 months. Outcomes (liver transplantation and death) at 1 year were also recorded. Results: Three groups of patients were identified. Pre-ACLF patients (n = 218) developed ACLF and had 3-month and 1-year mortality rates of 53.7% and 67.4%, respectively. Unstable decompensated cirrhosis (UDC) patients (n = 233) required >= 1 readmission but did not develop ACLF and had mortality rates of 21.0% and 35.6%, respectively. Stable decompensated cirrhosis (SDC) patients (n = 620) were not readmitted, did not develop ACLF and had a 1-year mortality rate of only 9.5%. The 3 groups differed significantly regarding the grade and course of systemic inflammation (high-grade at enrollment with aggravation during follow-up in pre-ACLF; low-grade at enrollment with subsequent steady-course in UDC; and low-grade at enrollment with subsequent improvement in SDC) and the prevalence of surrogates of severe portal hypertension throughout the study (high in UDC vs. low in pre-ACLF and SDC). Conclusions: Acute decompensation without ACLF is a heterogeneous condition with 3 different clinical courses and 2 major pathophysiological mechanisms: systemic inflammation and portal hypertension. Predicting the development of ACLF remains a major future challenge. Lay summary: Herein, we describe, for the first time, 3 different clinical courses of acute decompensation (AD) of cirrhosis after hospital admission. The first clinical course includes patients who develop acute-on-chronic liver failure (ACLF) and have a high short-term risk of death - termed pre-ACLF. The second clinical course (unstable decompensated cirrhosis) includes patients requiring frequent hospitalizations unrelated to ACLF and is associated with a lower mortality risk than pre-ACLF. Finally, the third clinical course (stable decompensated cirrhosis), includes two-thirds of all patients admitted to hospital with AD - patients in this group rarely require hospital admission and have a much lower 1-year mortality risk. (C) 2020 European Association for the Study of the Liver. Published by Elsevier B.V.
Keywords: Chronic liver disease; Non-elective admission; Acute complications; Outcome; Risk factors; CHRONIC LIVER-FAILURE; INFLAMMATION; MORTALITY; SCORE